2020
DOI: 10.1038/s41598-020-67392-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cross-frequency coupling following closed-loop auditory stimulation in non-rapid eye movement sleep

Abstract: Regional changes of non-rapid eye movement (NREM) sleep delta and sigma activity, and their temporal coupling have been related to experience-dependent plastic changes during previous wakefulness. These sleep-specific rhythms seem to be important for brain recovery and memory consolidation. Recently, it was demonstrated that by targeting slow waves in a particular region at a specific phase with closed-loop auditory stimulation, it is possible to locally manipulate slow-wave activity and interact with training… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…In support of this argument, we observed that the number of attempts in the down-phase group was lower than in the other groups at motor-training day 1, indicating that before any memory consolidation process took place, these animals already performed worse than their counterparts did. On the other hand, memory consolidation, a process at least partially mediated by spindles (Diekelmann & Born, 2010) in which specific synapses are strengthened, is also potentially sensitive to CLAS (Krugliakova et al, 2020; H.-Viet V. Papalambros et al, 2017). In fact, we did observe positive correlations between sigma -potentially a proxy for spindles (Holz et al, 2012) -during motor-training days 1-4 and success rate on motor-training day 4.…”
Section: Functional Validation Rodent Clas: Altered Behavioral Performance Upon Phase-targeted Clas In Healthy Ratsmentioning
confidence: 64%
See 1 more Smart Citation
“…In support of this argument, we observed that the number of attempts in the down-phase group was lower than in the other groups at motor-training day 1, indicating that before any memory consolidation process took place, these animals already performed worse than their counterparts did. On the other hand, memory consolidation, a process at least partially mediated by spindles (Diekelmann & Born, 2010) in which specific synapses are strengthened, is also potentially sensitive to CLAS (Krugliakova et al, 2020; H.-Viet V. Papalambros et al, 2017). In fact, we did observe positive correlations between sigma -potentially a proxy for spindles (Holz et al, 2012) -during motor-training days 1-4 and success rate on motor-training day 4.…”
Section: Functional Validation Rodent Clas: Altered Behavioral Performance Upon Phase-targeted Clas In Healthy Ratsmentioning
confidence: 64%
“…Our tool, thus, may be utilized to disentangle the exact effects of CLAS-modulated SWS on rodent cognition. Further, CLAS can be strategically combined with other tools, such as multiunit-activity recording, and provide crucial insight into the underlying neuronal mechanisms of auditory modulated slow waves and sigma (Krugliakova et al, 2020), and their functional role on learning and memory.…”
Section: Functional Validation Rodent Clas: Altered Behavioral Performance Upon Phase-targeted Clas In Healthy Ratsmentioning
confidence: 99%
“…Although EEG slow waves are a global cortical phenomenon during sleep [ 22 ], slow waves may be different in amplitude and phase across different brain regions. Slow oscillations during NREM sleep propagate from the medial frontal cortex to the medial temporal lobe [ 23 ] and can be regulated locally [ 24 , 25 ]; therefore, the effect following the stimuli presentation may be attributable to a particular brain region only [ 26 ]. It is not excluded, therefore, that the slight EEG fluctuations around baseline following the light stimulus ( Figure 4 ) may indeed represent visual-evoked potential (VEP) that would be more visible at the occipital region.…”
Section: Discussionmentioning
confidence: 99%
“…Following the acoustic stimulation, we received event-related responses containing spectral components (P200, N350, P450, N550, and P900) that are characteristic of stimulation-evoked K-complexes [ 21 ]. A convincing explanation of the closed-loop stimulation effects is that K-complexes externally evoked by stimulation time-locked to a particular phase of slow waves promote further synchronization of endogenous slow waves [ 8 , 26 ]. In our study, acoustic stimuli were delivered at the decay part of the slow wave up-phase in a relatively broad time range of the excitatory up-state of slow waves.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of auditory stimulation studies have used the closed-loop method; that is, utilising the ongoing EEG activity to deliver auditory stimuli in synchrony with the brain's endogenous rhythm [13,14,16,17,19,[21][22][23][24][25][26][27][28][29][30][31]32]. One study, however, used an open-loop protocol in which the ongoing EEG data had no bearing on the timing of stimulus delivery [33].…”
Section: Closed-loop Versus Open-loop Methodsmentioning
confidence: 99%